Development of Smart Pocket Learning Media to Improve the Ability to Recognize Number Concepts in Children Aged 5-6 Years - Delpiyani Delpiyani; Imam Tabroni; Benjamin Brunel; Milton Alan (Journal of Computer Science Advancements, 2023)
This study aims to produce valid Smart Pocket learning media to improve symbolic thinking skills in children aged 5-6 years. This research is a development research with the development model used by Sugiyono. In this study, researchers only used 7 (seven) stages, namely knowing problems and potential, data collection, product design, design validation, design revision, product trials and product manufacturing. The next stage was not carried out due to cost and time constraints. The data collection technique used is a questionnaire, where the questionnaire is validated by material experts, media experts and educators. The type of data generated is quantitative and qualitative data. The average percentage result of the pretest conducted on 3 children is 10.3%, proving that the child's condition is still in the stage of starting to develop. Then the posttest is carried out, namely the condition after the child is given Smart Pocket media, the average percentage result of this posttest is 16% which proves that the child has changed the condition to develop as expected. So it can be concluded that Smart Pocket media to improve the ability to think symbollically for children aged 5-6 years has met the criteria for validity.